DEATH AND GRIEF IN INTERGENERATIONAL SERVICE LEARNING: EXPLORATIONS FROM THE FIELD. (20th December 2022) - Bartlett, Sara; Solomon, Phyllis
Abstract: Intergenerational service-learning has been established as an effective pedagogical strategy for undergraduate gerontology education but can challenge students and instructors alike if an older adult participant dies during such a program. Currently, there is a lack of literature to provide guidance to instructors about how to address such an event. Examination of a case study of such an occurrence during the Lives Well Lived intergenerational service-learning program seeks to advance the field by describing an example of such an event and how an instructor might seek to address it. Grief literature, including theories such as Kübler-Ross' stage model, Worden's TEAR model, and Wortman and Silver's approach, as well as Doka's concept of disenfranchised grief are examined and applied to this challenging situation. Applying these theories as a framework, recommendations are given for addressing death and grief in service-learning including: (1) assessment of the course, instructor, student, and situation; (2) creating opportunities for grief processing and (3) resources for on and off campus grief and instructor support. Providing education on death, grief and grieving as integral course content and allowing student choice in how to proceed with the project should a death occur are key recommendations to consider. Implications call for more research related to this topic.